حقوق التأليف والاختراع بين الفقه الإسلامي والقانون :‏ ‏‏المالديف نموذجا /‏ - موسى، إبراهيم زكريا (Kulliyat Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This research explores the status quo of intellectual property rights in the Republic of Maldives and analyses relevant legislative reforms and enforcement methods of safeguarding these rights from an Islamic perspective. In this regard, the main aim of this study is to contribute towards contemporary legal reformation in the Maldives. Moreover, this study attempts to explain the legality of the issue from an Islamic perspective by addressing ways to harmonize intellectual property laws with Islamic Jurisprudence. Seeking to analyze the role and nature of Islamic Jurisprudence in the protection of Intellectual property rights, this research uses both qualitative and investigative methods along with the application of analytical and comparative methods. The primary sources of information used in the analysis come from a wide array of materials including relevant academic literature as well as magazine and newspaper articles, letters, web pages, and opinions of both Islamic and legal jurists about various copyright-related controversies. Examining these sources – both mainstream and obscure – illustrates the diversity of thinking on copyright issues. Such diverse (and often contradictory) views highlight the importance of formulating an alternative Islamic framework for copyrights in the Maldives. Important findings are gathered at the end of the study. Firstly, in order to maintain a balanced protection mechanism among all sectors of the society, the rights of authorship and invention are protected by Islamic Jurisprudence and all necessary measures are taken to guarantee these rights while preventing all that lead to injustice. Secondly, imbalances in the usage of intellectual property between owners and consumers rise due to misconceptions in differentiating between tangible and intangible rights. Insight into Islamic Jurisprudence as well as conventional law leads to the conclusion that Intellectual property rights should strike a balance between the interest of the individual and that of the society. The study concludes with recommendations and proposals for the improvement of protecting the rights of authorship and invention in Maldives by enacting relevant laws derived from the fundamentals of Islamic jurisprudence. It also emphasizes the importance of protecting Maldivian folklores within such legislation. The study also provides proposals that will positively influence in creating awareness on the importance of protecting Intellectual rights while emphasizing the need for adopting a criminal justice system that would ensure that these rights would not be trespassed with impunity.